Air leaks and vasopressin release. Issue 11 (November 1990) - McIntosh, N; Prakash, P; Smith, A
Abstract : Eleven very low birthweight babies being ventilated for respiratory problems during the first week of life developed air leaks on 22 occasions. On 16 out of 19 occasions the infants showed increases in urinary excretion of vasopressin after these events and on 10 occasions out of 13 there was a rise in the plasma arginine vasopressin concentration. The peripheral signs of the syndrome of inappropriate antidiuretic hormone release were seen on only one occasion in response to the sometimes high vasopressin concentrations.